THE SIGNIFICANCE OF THE METHOD OF ULTRASONIC RESEARCH OF A THYROID GLAND WITH CONTRAST ENHANCEMENT IN THE DIFFERENTIAL DIAGNOSIS OF FOCAL NODULAR FORMATIONS - D. A. Rakitina; A. M. Belyaev; Z. A. Radzhabova; E. V. Kostromina; M. A. Kotov; R. A. Nazhmudinov (Опухоли головы и шеи, 2017)
Introduction. Currently thyroid nodules are a widespread problem in clinical oncology and head and neck cancer, malignant focal lesions constitute more than 15–20  %. Accurate diagnosis is very important and determines treatment, as well as the volume of surgical intervention.Objective – determination of the diagnostic value of the method of contrast-enhanced ultrasound in the diagnosis of thyroid cancer. Reference materials were the results of the histological study of surgical specimens.Method. Performed a retrospective analysis of medical records of 42 patients who underwent surgery at the surgical department of head and neck tumors on the verified thyroid cancer in the N.N. Petrov Research Institute of Oncology at the Ministry of Health of Russia. The number of female patients was 36 persons (85.5 %), the number of men was 6 people (14.5 %). The average age of patients among men was 55.5 years, women – 46 years. All patients underwent surgical treatment in the amount of extirpation of the thyroid gland – 16 patients (37.5 %), hemithyroidectomy – 26 patients (62.5 %).Results. The sensitivity of ultrasound with contrast in the diagnosis of cancer of the thyroid gland was 94.11 %, specificity was 87.5 %, diagnostic accuracy – 92.8 %.Conclusions. The technique of ultrasound nodules thyroid with intravenous contrast enhancement has an excellent diagnostic properties, allowing to identify and verify thyroid cancer is 8 % more accurately in comparison with standard ultrasound technique.